(untitled) (Journal of Mechanical Engineering, 2010)
In condensation over horizontal tubes where the wall temperature is not measured directly, the Wilson plot is used to determine the cooling side heat transfer coefficient. Conventionally, the variation in Nusselt number, Nu, with condensate side temperature drop, DTs, which accompanies change of cooling side flowrate, is assumed to be Nu µ 1/DTsn with n = 0.25. This is the free convention condensation value. In this paper a technique is devised, not only to check the accuracy of this assumption in the usual vapor side cross flow situation, but also to determine the effect on this accuracy of allowing the index n to vary. In a case study the best agreement between DTs assumed and the value obtained using the cooling side heat transfer coefficient which resulted from the Wilson plot, occurred at n = 0.21. Based on the random errors in the measured data, a linear regression taking into account the errors in both Wilson plot coordinates gave the cooling side heat transfer coefficient and its uncertainty. Keywords: Heat transfer; condensation; Wilson plots. DOI: 10.3329/jme.v41i1.5360 Journal of Mechanical Engineering, Vol. ME 41, No. 1, June 2010 31-41